Using Digital Technology / by Ben Hubbard - Hubbard, Ben, 1973- (Chicago, Illinois : Capstone, 2017)
Explains how people use computers to browse the Internet, get movies and music, store files, play games, and perform other functions.
Includes index
Keywords: Internet -- Juvenile literature; Computers and children -- Juvenile literature